ANALISIS PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP TAX AVOIDANCE (PENGHINDARAN PAJAK) (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2009-2013) - Winda Agustina Tiarawati (Jurnal Akuntansi Indonesia, 2015)
Corporate Social Responsibility disclosure is a way to improve the company’s reputation in public. One way to do that is to directly contribute the welfare of the country through tax regulations that imposed in CSR. Many companies are burdened with these things and trying to find ways to minimize the burden tax were suspended in CSR, one way is through the tax avoidance. Research with the title Analysis Influence of Corporate Social Responsibility Disclosure with Tax Avoidance used the control variable profitability, leverage, type of industry, sales growth and size of the company. This study used a descriptive study with secondary data types. The population in this study are all companies listed on the Stock Exchange Manufacturing 2009-2013 period. The sample in this study is a Manufacturing company in Indonesia which are selected using purposive sampling method. The total sample is 115 companies. The data obtained were analyzed using SPSS version 16. The method of analysis using multiple linear regression with multiple testing was conducted on the normality test, multicollinearity, heteroscedasticity test, autocorrelation test, F test, test and test determination coefficient t statistic. The analysis showed that for normality test results indicate that the data are normally distributed. Multikolnearitas test showed that no symptoms of multicollinearity. Heteroscedasticity testing that the regression model did not produce symptoms of heteroscedasticity. While the autocorrelation test indicates that there is no autocorrelation regression equation. Results of hypothesis testing showed significant value on the t test of 0.028 <0.05, which means that the hypothesisis accepted. The conclusion of this study indicate that CSR has a negative effect with tax avoidance.